2015
DOI: 10.1002/acr.22578
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Realigning Brace on Tibiofemoral Contact Stress

Abstract: Objective. To determine the degree to which focally elevated tibiofemoral joint contact stress is reduced by using a frontal plane realigning brace. Methods. Fifteen volunteers (9 women) with unicompartmental tibiofemoral osteoarthritis underwent weight-bearing radiographic imaging at 15-208 and 5-108 of knee flexion with and without an UnloaderOne knee brace. Discrete element analysis was used to estimate compartment-specific contact stress distributions. Paired t-tests were used to assess the differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Obviously the state of tissue structure and biology alter the effects of biomechanics ( Fig. 1) 17,65 .…”
Section: Intrinsic Factors Modifying Interrelationships Between Oa Anmentioning
confidence: 99%
“…Obviously the state of tissue structure and biology alter the effects of biomechanics ( Fig. 1) 17,65 .…”
Section: Intrinsic Factors Modifying Interrelationships Between Oa Anmentioning
confidence: 99%
“…Two studies confirmed that the brace significantly reduced the peak contact stress in the medial compartment while increased in the lateral compartment [ 51 , 55 ]. One study [ 53 ] showed that the mean contact stress and contact area of the medial compartment were not changed when the knee joint was at 5-10° and 15-20° flexion states.…”
Section: Resultsmentioning
confidence: 99%
“…15 The present study indicates that articular contact stress, which accounts for both bone structure and cartilage morphology, is associated with 84-mo worsening of knee pain. In addition, contact stress estimates can provide clinicians with evidence to select appropriate treatments for reducing articular contact stress in the knee joint, [35][36][37] as well as improving knee symptoms, physical function, and potentially delaying or preventing the progression of knee OA. Laterally wedged insoles are commonly prescribed to shift loading from the medial to lateral compartments in patients with medial knee OA.…”
Section: Discussionmentioning
confidence: 99%
“…6,41 Contact stress estimates could help both identify patients with early knee OA most likely to benefit from these conservative treatments as well as to evaluate the biomechanical effects. Segal et al 37 used DEA-based contact stress estimates to assess the biomechanical effect of a single-upright brace for the realignment of the tibiofemoral joint in participants with unicompartmental tibiofemoral OA.…”
Section: Discussionmentioning
confidence: 99%